Gender effects in the battle of the sexes: A tale of two countries - Fabrizio Adriani; Monika Pompeo; Silvia Sonderegger (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
In a setting where inequality is ingrained and largely unavoidable (battle of the sexes), we investigate whether subjects condition their behaviour on the gender of their co-player. In order to identify the role of culture and gender norms, we run the experiment in two countries, Norway and India, characterised by very different levels of gender inequality. We find different patterns of gender effects in the two countries. In India, subjects are more 'hawkish' when facing a woman. This occurs only for lower education subjects and is observed primarily in female participants. Highly educated Indian participants do not discriminate between male and female co-players. In Norway, the gender effect is the opposite of what observed in India: it is present only in highly educated male participants, and takes the form of subjects becoming more 'hawkish' when facing a man. Our evidence suggests that these gender effects may be due to subjects experiencing different levels of inequality aversion depending on the gender of their co-player, in a manner that is mediated by their culture and gender norms.
Keywords: C70; C99; J16; 330; gender; social norms; coordination; culture; inequality aversion